RELATIONSHIP BETWEEN OFFICE DESIGN ON EMPLOYEE’S PRODUCTIVITY AT SAJ HOLDINGS SDN. BHD. - Nur Adilla Roslani; Siti Nurul Akma Ahmad; Nor Maslia Rasli Samudin; Nurhafizah Mohd Zolkapli; Siti Norashikin Bashirun (International Journal of Accounting, Finance and Business, 2021)
The productivity improvements have been recognized to have a major impact oneconomic growth and a higher standard of living on many economic and social phenomena.Companies must continuously improve their productivity to stay profitable. Therefore, thisresearch aims to study the relationship between office design which focuses on lighting and noiseon employee productivity. The study was conducted at SAJ Holdings Sdn. Bhd. which involved140 respondents through simple random sampling. The researcher used the structuredquestionnaire from the previously published research as the measurement for this study. A setof questionnaires was distributed to the respondent and the data collected were analyzed usingStatistical Package for Social Science (SPSS). The result obtained shows that there was asignificant relationship between office design (noise and lighting) towards employeeproductivity. Also, the level of employee productivity at SAJ Holdings Sdn. Bhd. is aboveaverage. Thus, this study concluded that office design is a crucial factor that drives towardsincreasing employee productivity and the entire organization's success as well as in achievingbusiness goals, vision, and mission.